THE EFFECTIVENESS OF INTERFERON BETA-1A IN MANAGEMENT OF MULTIPLE SCLEROSIS: A CASE REPORT - Puspitasari, Vivien; Sutanto, Anyeliria; Pangestu, Aristo Rinaldi (MNJ (Malang Neurology Journal), 2020)
Multiple sclerosis is a chronic autoimmune disease that attacks myelin in the central nervous system. About 2.5 million people worldwide have been diagnosed with multiple sclerosis. Its clinical presentation could vary according to the location of the lesion. Interferon beta is the most commonly used as immunomodulation therapy. However, its effectiveness for long-term use is still questionable. We report a case of 24-year-old woman with complaints of ataxia and limb weakness which were diagnosed as multiple sclerosis relapsing remitting (MSRR) and treated with interferon beta 1a for five years. During routine interferon beta 1a treatment three times a week, patient has still experienced four episodes of relapse in spite of good compliance. Hence, the rare presence of neutralizing antibodies was suspected. It commonly occurs after a year of interferon therapy, which is consistent with the patient’s treatment history. Further biomarker testing of drug-specific antibodies might be valuable to find out the possibility of interferon resistance